Potential Role SDR Diversified Currency Portfolios Central Bank. (IMF Working Papers; Working Paper ;, 1988)
This paper compares the SDR in terms of its risk-return characteristics relative to those of its five components and, on this basis, finds that the SDR has performed favorably over the period under review. In addition, several efficient portfolios including the SDR and its components are computed. These computations provide evidence that in many cases the SDR has a major weight, particularly in those portfolios which involve minimum risk and therefore would appear to be most appropriate for reserve holders. Thus, the evidence presented suggests that the SDR can play a major role in the international reserve portfolios of central banks.